2015
DOI: 10.1002/jhbp.268
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter comparative study of laparoscopic and open distal pancreatectomy using propensity score‐matching

Abstract: Background Laparoscopic distal pancreatectomy has been shown to be associated with favorable postoperative outcomes using meta-analysis. However, there have been no randomized controlled studies yet. This study aimed to compare laparoscopic and open distal pancreatectomy using propensity score-matching. Methods We retrospectively collected perioperative data of 2,266 patients who underwent distal pancreatectomy in 69 institutes from 2006-2013 in Japan. Among them, 2,010 patients were enrolled in this study and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 24 publications
6
75
0
Order By: Relevance
“…However, most pancreatic surgeons encounter complications after DP, especially postoperative pancreatic fistula (POPF). The incidence of POPF after DP has been reported to range from 18.6 to 64.9 % [2][3][4]. POPF causes a variety of postoperative complications, such as intra-abdominal abscess, delayed gastric emptying, and postoperative hemorrhage, due to pseudoaneurysm rupture.…”
Section: Introductionmentioning
confidence: 99%
“…However, most pancreatic surgeons encounter complications after DP, especially postoperative pancreatic fistula (POPF). The incidence of POPF after DP has been reported to range from 18.6 to 64.9 % [2][3][4]. POPF causes a variety of postoperative complications, such as intra-abdominal abscess, delayed gastric emptying, and postoperative hemorrhage, due to pseudoaneurysm rupture.…”
Section: Introductionmentioning
confidence: 99%
“…First reported in 1994, laparoscopic distal pancreatectomy (LDP) is being performed with increasing frequency worldwide despite a lack of randomized data supporting this approach over standard open distal pancreatectomy (ODP). Approximately one quarter of all DPs are performed using minimally invasive approaches [5].Drs Nakamura and colleagues from 69 medical centers in Japan used a sophisticated statistical method (propensity score matching -PSM) to address the comparison of two surgical techniques (LDP and ODP) for removing the left side of the pancreas [6]. The key findings between the two cohorts after PSM are that compared with ODP, LDP is associated with lower blood loss (254 ± 384 vs. 499 ± 740, <0.001), fewer blood transfusion (4% vs. 6.8%, P = 0.02), fewer grade B and C POPF (18.4% vs. 28.2%, P < 0.001), a higher percentage of splenic preservations (29.9% vs. 13.2%, P < 0.001), and shorter hospital stays (18.8 ± 14.7 vs. 23.2 ± 18.8, P = 0.001).…”
mentioning
confidence: 99%
“…Similarly, a review on laparoscopic surgery published in 2016 concluded that laparoscopic DP can be safely performed in high-volume centers, but that randomized controlled trials still have to confirm the effectiveness of the procedure [23]. A large propensity score-matching comparative study from Japan even showed that morbidity was diminished with laparoscopic DP along with intraoperative transfusion, and LoS [24]. Only the operative time was longer.…”
Section: Discussionmentioning
confidence: 99%